47 Novel inflammatory biomarkers of coronary plaque instability and rupture. (5th October 2017) - Bajrangee, A; Mahabir, S; Brennan, M; Cox, D; Maree, AO
Abstract : Background: Plaque inflammation precipitates rupture the sequel of which is coronary thrombosis and myocardial cell death. A panel of inflammatory biomarkers to detect plaque instability may increase diagnostic accuracy in chest pain patients. Interleukin 15 receptor alpha (IL-15 Rα) a receptor for interleukin 15, which modulates T cell proliferation and Galectin -3 (Gal-3) a lectin that is upregulated when monocytes differentiate into macrophages, are both intrinsically involved in plaque maturation and rupture. We aimed to determine their utility in detecting plaque rupture and instability. Methods: Consecutive patients presenting with chest pain to the emergency department of St James's Hospital, Dublin or those referred directly for angiography were recruited between September 2014 to December 2015. Patients were divided into non-cardiac chest pain (NCCP), stable angina (SA) and acute coronary syndrome (ACS-unstable angina, NSTEMI and STEMI) based on clinical presentation, chest pain scoring tools (HEART, TIMI and GRACE score), electrocardiogram (ECG) changes, troponin measurements and angiographic data. Serum concentration of Gal-3 (0.3–10 ng/ml) and IL-15 Rα (31.25–2000 pg/ml) was determined by ELISA ( R and D Systems Inc) . Results: Patients (n=184), with NCCP (n=83), SA (n=51) and ACS (n=50) were recruited. The mean age for the entire cohort was 61± 12 years with 65% males. The mean concentration of IL-15 Rα was 728± 74 pg/ml in ACS patients, 629±76 pg/ml in SA and 515± 54 pg/ml in NCCP (p= 0.05). The mean Gal-3 concentration was 9.8± 2.6 ng/ml in ACS, 9 ± 2.3 ng/ml in SA and NCCP was 8.4± 0.3 ng/ml (p = 0.02). Both Gal-3 and IL-15 Rα were highest in patients with ACS. In patients with UA who were troponin negative and less likely to have undergone plaque rupture the mean Gal- 3 concentration was 9.9 ± 2.9 ng/ml (p= 0.03) and for IL-15 Rα it was 819± 608 pg/ml (p=0.04) which was significantly higher than those with NCCP and SA. In patients presenting with ACS the correlation between IL-15 Rα and Gal-3 was r= 0.5 (p=0.02). The correlation in UA was stronger with r=0.6 (p=0.02). Conclusion: In patients with ACS both IL-15 Rα and Gal-3 were significantly elevated when compared to those with NCCP and SA. In patients with UA who were troponin negative and likely presented with unstable plaque, IL-15 Rα and Gal-3 were significantly elevated with a high degree of correlation. Both markers may indicate plaque instability.